An Analysis Of Power Transformer Performance Reliability On The Effect Transient Recovery Voltage - Arnanda Putra; Solly Aryza; Zuraidah Tharo (Sean Institute, 2024)
Technologies a power transformer is a crucial component in an electric power system that functions to change electric voltage from one level to another. Reliable transformer performance is essential to ensure the continuity of electricity supply and prevent significant losses. One phenomenon that can affect transformer reliability is Transient Recovery Voltage (TRV). This paper described the reliability of power transformer performance against the influence of TRV through simulations and experimental measurements. The research methodology includes literature review, mathematical modeling, simulation using electric power system analysis software, and laboratory testing. The research results show that TRV has a significant influence on transformer reliability, especially under conditions of major disturbances. Recommendations for mitigating the impact of TRV include the use of additional protective devices such as surge arresters and improving the quality of transformer insulation. By understanding the influence of TRV on transformer performance, it is expected to increase the reliability and operational lifespan of power transformers, as well as reduce the risk of economic losses due to transformer damage. This research makes an important contribution to the development of protection and maintenance techniques for power transformers in modern electric power systems.